Hazard Mapping in Urban Environmental Protected Areas: Tijuca National Park - Santos, Rodrigo B.; Dourado, Francisco; Schumm, Leonard (Revista Brasileira de Gestão Urbana, 2024)
Tijuca National Park (Parque Nacional da Tijuca - PNT), in the Carioca Hills, Rio de Janeiro, faces often landslides. This threatens the environment and the infrastructure, such as Estrada do Redentor, which connects the Paineiras Visitor Center (CVP) to the Floresta Visitor Center Sector. Due to the lithological-structure characteristics and the status of urban protection area, many methodologies are not suitable for risk mapping and management. Therefore, a methodological adjustment was developed to identify landslide-prone areas by quantifying, understanding, and spatializing events and conditioning factors. Using GIS tools, we collected data on geological structures and infrastructure to assess risk. As a result, a concentration of high-risk areas was identified near the CVP. Medium risk areas are centralized, while from the middle of the road to Alto da Boa Vista, the predominant areas range from low to medium risk. The most common factors are cracks in the road, loose blocks on the slopes, and cuts in the road. Therefore, on Redeemer Road, there is a combination of factors affecting safety, such as lithological-structure and geomorphological aspects, rainfall, slope and lack of maintenance of existing structures.